2019
DOI: 10.1111/cas.14249
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular claudin‐1 at the invasive front of tongue squamous cell carcinoma is associated with lymph node metastasis

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made. AbstractClaudins are the major component of tight junctions, which form a primary barrier to paracellular diffusion and maintain cell polarity in normal epithelia and endothelia. In cancer cells, claudins play additional roles besid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 37 publications
2
9
0
2
Order By: Relevance
“…2 c). A similar change in claudin localization has been reported for CLDN1 in breast cancer, colon cancer and tongue carcinoma; the localization of CLDN1 changes from the membrane to the cytoplasm as the malignancy progresses 28 , 29 .…”
Section: Discussionsupporting
confidence: 77%
“…2 c). A similar change in claudin localization has been reported for CLDN1 in breast cancer, colon cancer and tongue carcinoma; the localization of CLDN1 changes from the membrane to the cytoplasm as the malignancy progresses 28 , 29 .…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, in colorectal cancer and uterine cervical SCC tissues, CLDN12 was localized in the cytoplasm. Although we do not know why CLDN12 possesses distinct subcellular localization as described above, it has been reported that the CLDN1 localization is altered from cell membranes to cytoplasm at the invasion front of tongue SCC tissues [ 36 ].…”
Section: Discussionmentioning
confidence: 92%
“…Nuclear claudins are mostly found in malignant tissues, suggesting their role in cancer. They are always found in complexes containing other proteins, such as b-catenin, YAP, ZO-1, ZO-1 nucleic acid-binding protein (ZONAB), and cyclin D1, and induce retention of such molecules in the nucleus to enhance cell proliferation and cancer progression (48)(49)(50)(51)(52). The underlying mechanisms contributing to their translocation are not well understood but may involve phosphorylation by protein kinases (53).…”
Section: Claudins As Tumor Promotersmentioning
confidence: 99%